Application of Small Epigenetic Modulators in Pediatric Medulloblastoma - Zwergel, Clemens; Romanelli, Annalisa; Stazi, Giulia; Besharat, Zein Mersini; Catanzaro, Giuseppina; Tafani, Marco; Valente, Sergio; Mai, Antonello (Frontiers in Pediatrics, 2018)
Medulloblastoma is one of the most frequent among pediatric brain tumors, and it has been classified in various subgroups. Some of them already benefit from quite good therapeutic options, whereas others urgently need novel therapeutic approaches. Epigenetic modulators have long been studied in various types of cancer. Within this review, we summarize the main preclinical studies regarding epigenetic targets (such as HDAC, SIRT, BET, EZH2, G9a, LSD1, and DNMT) inhibitors in medulloblastoma. Furthermore, we shed light on the increasing number of applications of drug combinations as well as hybrid compounds involving epigenetic mechanisms. Nevertheless, in the studies published so far, mainly un-specific or old modulators have been used, and the PKs (brain permeability) have not been well evaluated. Thus, these findings should be considered as a starting point for further improvement and not as a final result.